The Application of Niklas Luhmann’s Theory of Autopoesis to the Analysis of the System of Law - Sidrys, Inga (Sociologija. Mintis ir veiksmas, 2001)
Social systems theory and, more particularly, concepts like autopoesis, self-referentiality, autonomy, have been the subject of intensive discussion in the social sciences during the last decades of the 20th century. Niklas Luhmann was among the first who recognized the need to incorporate the theory of autopoesis into his evolutionary study of law. In this article, I re-examine Luhmann’s theoretical analysis of the concept of law in the light of a general theory of social systems. His theoretical development focuses on the legal system as an autopoietic and self-referential system. Luhmann argues that the legal system is normatively closed, because it produces its own elements as legally relevant units and, at the same time, it is a cognitively open as it remains oriented to its environment despite its “closedness”. The present study reviews and comments upon key concepts in Luhmann theory which include autopoietic system, normatively closed and cognitively open systems, environment, legal system, expectations, norms, and binary code. Although Rottleuthner and others have criticised Luhmann for his great passion to theoretical abstractions, the author of this article thinks that Luhmann deserves our attention as an important contemporary representative of systems science in sociology.